The The Effectivenees of Solution Focused Brief Therapy Group Counseling to Reduce Social Anxiety for Vulnerable Children - Fiana, Anis Lud; Wibowo, Mungin Eddy; Sutoyo, Anwar (Universitas Negeri Semarang, 2022)
Social and family attention influences children development, including vulnerable children. The vulnerable children who lack of those attention will experience difficulties in adapting to environment, such as having low self-esteem, being ostracized, and being vulnerable to violate existing norms. Regarding the previous explanation, this study strived for examining the effectiveness of a group counseling service with solution focused brief therapy to reduce vulnerable children social anxiety. It used an experimental method with one group pretest-posttest design by involving 7 vulnerable children in SOS Children’s Village Semarang as the subjects. Findings indicated that the group counseling with solution focused brief therapy has been effective to reduce the social anxiety of the vulnerable children. Further, this treatment can be an alternative method for counselors or caregivers to reduce the vulnerable children social anxiety.